2018
DOI: 10.1021/acssuschemeng.8b00090
|View full text |Cite
|
Sign up to set email alerts
|

Ethylenediamine-Enabled Sustainable Synthesis of Mesoporous Nanostructured Li2FeIISiO4 Particles from Fe(III) Aqueous Solution for Li-Ion Battery Application

Abstract: Engineering of nanostructured lithium iron silicate (LFS) particles is pursued via a novel benign synthesis approach seeking to understand the crystalline particle formation process and its impact on energy storage capacity. Specifically, mesoporous Li 2 FeSiO 4 nanostructured particles are synthesized via a novel dual-step process involving organic-assisted hydrothermal precipitation from concentrated Fe(III) (1 mol/L) aqueous solution followed by reductive (5 vol % H 2 ) thermal transformation of the precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…It is of interest to evaluate the effect of these metastable phases on the electrochemical performance of battery materials, such as the two-phase reaction in a LiFePO 4 cathode 7,8 and the solid-state reaction in Li 2 FeSiO 4 cathodes. 6,9 However, this conventional perspective on the structural evolution can be obscured, 10,11 if a size effect is considered, because the increasing specific surface area of the electrode materials enhances the surficial nonfaradic Li storage behavior, which always yields a sloped electrochemical curve during electrochemical cycles. With decreasing particle size, the side reactions and surface activity of the electrode materials increase during battery cycles or exposure to the air.…”
Section: Introductionmentioning
confidence: 99%
“…It is of interest to evaluate the effect of these metastable phases on the electrochemical performance of battery materials, such as the two-phase reaction in a LiFePO 4 cathode 7,8 and the solid-state reaction in Li 2 FeSiO 4 cathodes. 6,9 However, this conventional perspective on the structural evolution can be obscured, 10,11 if a size effect is considered, because the increasing specific surface area of the electrode materials enhances the surficial nonfaradic Li storage behavior, which always yields a sloped electrochemical curve during electrochemical cycles. With decreasing particle size, the side reactions and surface activity of the electrode materials increase during battery cycles or exposure to the air.…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al took Fe(NO 3 ) 3 Á9H 2 O, CH 3 COOLi, and gaseous silica as raw materials and used organic solvents ethylene glycol (EG) and ethylenediamine (EN) as precursors to prepare intermediate precipitates by organically assisted hydrothermal precipitation method. 26 Then, after annealing and heat treatment, Li 2 FeSiO 4 nanoparticles with particle sizes of about 50 nm (annealed at 400 C) and 200 nm (annealed at 700 C) were obtained, which is respectively denoted as LFS400 and LFS700, with the corresponding mechanism diagram shown in Figure 11. The discharge capacity of modified Li 2 FeSiO 4 nanometer cathode material at C/10 ratio is 170 mAh/g, and the capacity retention rate is about 90% after several cycles, showing good cycling stability.…”
Section: Reduce the Size Of The Materialsmentioning
confidence: 99%
“…Previous studies have indicated that lithium metal orthosilicates can provide higher capacity of up to 330 mA h g −1 which makes them potential options in LiB applications. The electrochemical performance of lithium metal orthosilicates is significantly influenced by the synthesis routes [96b] . Multiple lithium iron silicate synthesis routes have been reported, including solution and solid‐state synthesis methods, with their pros and cons.…”
Section: Energy Storage Using Mp‐fenssmentioning
confidence: 99%
“…This synthesis process was complicated due to the annealing process that requires higher temperature. To simplify the synthesis route and the reduction production cost of applying (Fe (II)) salt as the precursor, Wei et al [96b] . produced a mp‐C‐coated nanostructured lithium iron silicate based on Fe (III) salts with comparable capacity and stability to those derived from Fe(II) salts through a facile method.…”
Section: Energy Storage Using Mp‐fenssmentioning
confidence: 99%